The Potential of BioTP to Enhance Macronutrient Content in Household Organic Waste Compost - Prihastini, Lilis; Indraswati, Denok; Jayadi, Hurip (Jurnal Penelitian Kesehatan SUARA FORIKES, 2026)
Household waste is predominantly organic, consisting of food scraps, vegetables, and fruits that naturally decompose. However, the decomposition process may lead to environmental and health problems if not properly managed; therefore, appropriate waste management is essential. One method for managing household waste is composting. This study aimed to determine the potential of the bioinoculant BioTP to enhance macronutrient content in household organic waste compost. This research employed an experimental pretest–posttest with control design. Macronutrient levels (N, P, and K) in household organic waste were measured before and after the decomposition process in both the treatment group (with BioTP) and the control group. The data were analyzed using a t-test. The results showed that after decomposition, all macronutrients (N, P, and K) in the treatment group increased. The macronutrient content in all treatments met the standards for organic fertilizer. Statistical analysis before and after decomposition indicated a significant difference in nitrogen (N) levels in both the treatment and control groups (p < 0.05), whereas phosphorus (P) and potassium (K) levels showed no significant differences (p > 0.05). Comparison between the treatment and control groups also revealed no significant differences in N, P, and K levels (p > 0.05). In conclusion, BioTP has the potential to enhance macronutrient content in household organic compost; however, its effect has not yet reached an optimal level.Keywords: household organic waste; decomposition; bioinoculant; macronutrients